Approaching Local Elections: Intensifying Electronic Identity Card (E-ID) Registration for Gen-Z Civic Participation - Fatwa, Salma Auliya; Muhafidin, Didin (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2024)
This study analyzes the intensification of the mobile service program for recording Electronic Identity Cards (e-ID) ahead of the 2024 Regional Election in Cirebon City, which targets 4,387 high school students who have not yet recorded. Using a qualitative approach with a case study method, the research adopted Muchlis Hamdi's theoretical framework to analyze three dimensions of implementation: productivity, linearity, and efficiency. The data were collected through in-depth interviews with eight key informants, including Disdukcapil officials, the implementation team, and school representatives, supported by observations and documentation studies. The results indicated that the program achieved 74.18% of the effective target of 4,268 students in terms of productivity. This suboptimality can be attributed to demographic complexity and target group resistance. In terms of linearity, the program exhibited adequate balance and compatibility across five key domains: implementers who possessed the necessary competencies and qualifications; procedures, time, and cost aspects. Despite encountering infrastructure challenges, the optimization of limited resources in a cost-efficient manner. However, the budget aspect revealed dynamics that necessitated attention. The program exhibited a solution-oriented approach and operational flexibility in increasing first-time voter participation.